Occupational Health and Safety Issues in the Construction Industry in South Asia: A Systematic Review and Recommendations for Improvement - Bajracharya, Nasana; Magar, Pawan Rana; Karki, Suman; Giri, Suja; Khanal, Ashish (Journal of Multidisciplinary Research Advancements, 2023)
This paper explores the occupational health and safety issues faced by construction workers in South Asia, where construction is primarily conducted informally via local contractors. The study involved a systematic review of existing literature on occupational health and safety in the construction industry, with Nepal, India, and Bangladesh chosen as the focus countries. Despite the implementation of regulations and safety measures, accidents and injuries on construction sites continue to be prevalent, and there is a lack of investment in training and education programs, as well as regulatory oversight. The study identifies a lack of awareness, inadequate training, and poor working conditions as key factors contributing to the occupational health and safety issues faced by construction workers in South Asia. The paper concludes by providing recommendations to improve occupational health and safety, including greater investment in training and education programs, improved regulatory oversight, and addressing cultural and social factors that contribute to unsafe working conditions for construction workers in the region. The findings highlight the need for improved implementation of existing laws and regulations, as well as greater attention to the health and safety of construction workers in South Asia.